Green Campus: Analisis Konsumsi Energi Fosil Terhadap Indoor Environmental Quality - Alfarisi, Salman; Tauhida, Dina (Journal of Industrial Engineering and Technology, 2024)
The graphical abstract is presented in the manuscript.